Factors Determining Socio-Scientific Issues in STEAM Education to Enhance Problem-Solving Skills for Pre-Service Teachers: Development and Validation of a Measurement Model - Eko Hariyono; Laily Rosdiana; Mohammad Budiyanto; Muhammad Satriawan; Hasna Nabilah; Iqbal Ainur Rizki (Universitas Negeri Semarang, 2026)
This study aimed to develop and validate a measurement model of SSI–STEAM education for pre-service science teachers (PSTs), with particular attention to dimensions associated with problem-solving skill development. Using a cross-sectional survey design, data were collected from 173 PSTs enrolled in science education programmes in Indonesia. Exploratory Factor Analysis (EFA) and Confirmatory Factor Analysis (CFA) were conducted to identify and validate the latent constructs underpinning SSI–STEAM implementation. EFA results supported a clear two-factor model, consisting of enacted values and practices, affective learning, authentic contexts and activities, interdisciplinary thinking and integrated practices, and problem-solving skill reflection. CFA confirmed the adequacy of this structure, producing acceptable model-fit indices and satisfactory reliability and convergent validity across factors. To conclude, this study highlights the multidimensional nature of SSI–STEAM education and underscores the importance of value-driven instruction, interdisciplinary integration, authentic socio-cultural contexts, and reflective problem-solving in preparing PSTs to engage learners with complex real-world scientific issues. These insights offer valuable implications for curriculum design in science teacher education, which are also discussed.